Pasar Gambir, komik Cina & es Shanghai : sisik melik Jakarta 1970-an - Alkatiri, Zeffry J., 1960- (Depok : Masup Jakarta, 2010)
Essays on social life in Jakarta in the 1970s.
Includes bibliographical references (p. 177-178) and index.